Machine and web translator for English to Bangla using natural language processes (Daffodil International University Journal of Science and Technology, 2010)
The modern web contents are mostly written in English and developing a system with the facility of translating web pages from English to Bangla that can aid the massive number of people of Bangladesh. It is very important to introduce Natural Language Processing (NLP) and is required to developing a solution of web translator. It is a technique that deals with understanding natural languages and natural language generation. It is really a challenging job to building a Web Translator with 100% efficiency and our proposed Web Translator basically uses Machine Translator as its mother concern. This paper represents an optimal way for English to Bangla machine and the Web translation & translation methods are used by translator. Naturally there are three stages for MT but here we propose a translation system which includes 4 stages, such as, POS tagging, Generating parse tree, Transfer English parse tree to Bengali parse tree and Translate English to Bangla and apply AI. An innovation initiative has scope of being upgraded in future and hopefully this work will assist to develop more improved English to Bangla Web Translator. Keywords: Machine Translator, Web Translator, POS Tagging, Parsing, HTML Parsing, Verb Mapping DOI: 10.3329/diujst.v5i1.4382 Daffodil International University Journal of Science and Technology Vol.5(1) 2010 pp.53-61